Penerapan Artificial Intelligence Dalam Sistem Akuntansi Pariwisata Desa Adat Penglipuran - Fima Fahmawati; Deviana Indah Pratiwi; Ravenska Kayla Cahyana; Utami Puji Lestari (Journal Economic Insights, 2026)
The application of Artificial Intelligence (AI) in the tourism accounting system of Penglipuran Traditional Village, Bali, provides a solution to the challenges of manual financial recording methods. The main problems faced include limitations in recording transactions that are prone to errors, delays in financial reporting, and a lack of integration between digital payment systems and accounting reporting. This study used an observational method with a qualitative approach, through direct interviews with traditional leaders and observations of the village accounting workflow. The results show that the village accounting system is running well through the Tourism Village Management Agency, but there are still obstacles to efficiency and accuracy of recording. The application of AI has the potential to provide solutions such as automation in transaction recording, preparation of real-time financial reports, and predictive analysis to estimate the number of tourists. The results show that the application of AI can support the sustainability of tourism villages by increasing transparency, accountability, and assisting in data-driven strategic decision-making. It is hoped that the synergy between modern technology and local wisdom can maintain modern tourism governance while maintaining cultural identity. This study recommends the importance of training and mentoring local communities to be able to operate the AI ​​system optimally, while maintaining the security of financial data.